Patient Perceptions Correlate Weakly With Observed Patient Involvement in Decision-making in Orthopaedic Surgery. Issue 9 (September 2018) - Mertz, Kevin; Eppler, Sara; Yao, Jeffrey; Amanatullah, Derek F.; Chou, Loretta; Wood, Kirkham B.; Safran, Marc; Steffner, Robert; Gardner, Michael; Kamal, Robin
Abstract: Background: Shared decision-making between patients and physicians involves educating the patient, providing options, eliciting patient preferences, and reaching agreement on a decision. There are different ways to measure shared decision-making, including patient involvement, but there is no consensus on the best approach. In other fields, there have been varying relationships between patient-perceived involvement and observed patient involvement in shared decision-making. The relationship between observed and patient-perceived patient involvement in decision-making has not been studied in orthopaedic surgery. Questions/purposes: (1) Does patient-perceived involvement correlate with observed measurements of patient involvement in decision-making in orthopaedic surgery? (2) Are patient demographics associated with perceived and observed measurements of patient involvement in decision-making? Methods: We performed a prospective, observational study to compare observed and perceived patient involvement in new patient consultations for eight orthopaedic surgeons in subspecialties including hand/upper extremity, total joint arthroplasty, spine, sports, trauma, foot and ankle, and tumor. We enrolled 117 English-literate patients 18 years or older over an enrollment period of 2 months. A member of the research team assessed observed patient involvement during a consultation with the Observing Patient Involvement in Decision-Making (OPTION) instrument (scaled 1-100 with higher scores representing greater involvement). After the consultation, we asked patients to complete a questionnaire with demographic information including age, sex, race, education, income, marital status, employment status, and injury type. Patients also completed the Perceived Involvement in Care Scale (PICS), which measures patient-perceived involvement (scaled 1-13 with higher scores representing greater involvement). Both instruments are validated in multiple studies in various specialties and the physicians were blinded to the instruments used. We assessed the correlation between observed and patient-perceived involvement as well as tested the association between patient demographics and patient involvement scores. Results: There was weak correlation between observed involvement (OPTION) and patient-perceived involvement (PICS) (r = 0.37, p < 0.01) in decision-making (mean OPTION, 28.7, SD 7.7; mean PICS, 8.43, SD 2.3). We found a low degree of observed patient involvement despite a moderate to high degree of perceived involvement. No patient demographic factor had a significant association with patient involvement. Conclusions: Further work is needed to identify the best method for evaluating patient involvement in decision-making in the setting of discordance between observed and patient-perceived measurements. Knowing whether it is necessary for (1) actual observable patient involvement to occur; or (2) a patient to simply believe they are involved in their care can inform physicians on the best way to improve shared decision-making in their practice. Level of Evidence: Level II, therapeutic study.